Estimação de parâmetros genéticos de ovinos da raça Santa Inês utilizando modelos uni e bicaracterística - Carvalho, Geane Conceição (2014)
The objective of this study is to estimate genetic parameters for growth traits in sheep Santa Ines breed by Restricted Maximum Likelihood (REML). The (co)variance components and genetic parameters were estimated by MTDFREML Software (Multiple Trait Derivative-Free Restricted Maximum Likelihood). The characteristics evaluated in single and two-trait models were: birth weight (BW) and weaning weight (WW). In addition to the fixed effects of sex, contemporary group and parity type, we used the following random effects: direct genetic effect, maternal additive genetic and residual effects. The direct additive heritability estimates for BW were 0.20 and 0.21 for single and two-trait models, respectively. Heritability estimates for direct additive WW were 0.04 and 0.07 for single and two-trait models, respectively. The genetic correlation between BW and WW was 0.11, indicating that both traits should be worked on simultaneously.